Analysis of teacher intervention in elementary education to prevent grooming - Flores Mayorga, Marco Tulio (IE Revista de Investigación Educativa de la REDIECH, 2025)
The widespread use of the internet and social media has introduced new risks to social interactions. Teachers and parents are particularly concerned about the safety of minors. This exploratory study aimed to assess primary school teachers’ knowledge of online grooming—a form of child sexual abuse—and to explore the educational strategies they employ to protect their students. Through interviews with 12 teachers from four public schools in Zapopan, Jalisco, Mexico, we found that teachers were largely unaware of grooming. Our findings highlight the need for increased training to enable teachers to identify signs of online grooming in their students. Timely interventions by schools and families can help foster a culture of internet safety.